What explains inconsistencies in field‐based ecosystem mapping?. Issue 1 (24th February 2023) - Naas, Adam Eindride; Halvorsen, Rune; Horvath, Peter; Wollan, Anders Kvalvåg; Bratli, Harald; Brynildsrud, Katrine; Finne, Eirik Aasmo; Keetz, Lasse Torben; Lieungh, Eva; Olson, Christine; Simensen, Trond; Skarpaas, Olav; et al.
Abstract: Questions: Field‐based ecosystem mapping is prone to observer bias, typically resulting in a mismatch between maps made by different mappers, that is, inconsistency. Experimental studies testing the influence of site, mapping scale, and differences in experience level on inconsistency in field‐based ecosystem mapping are lacking. Here, we study how inconsistencies in field‐based ecosystem maps depend on these factors. Location: Iškoras and Guollemuorsuolu, northeastern Norway, and Landsvik and Lygra, western Norway. Methods: In a balanced experiment, four sites were field‐mapped wall‐to‐wall to scales 1:5000 and 1:20, 000 by 12 mappers, representing three experience levels. Thematic inconsistency was calculated by overlay analysis of map pairs from the same site, mapped to the same scale. We tested for significant differences between sites, scales, and experience‐level groups. Principal components analysis was used in an analysis of additional map inconsistencies and their relationships with site, scale and differences in experience level and time consumption were analysed with redundancy analysis. Results: On average, thematic inconsistency was 51%. The most important predictor for thematic inconsistency, and for all map inconsistencies, was site. Scale and its interaction with site predicted map inconsistencies, but only the latter were important for thematic inconsistency. The only experience‐level group that differed significantly from the mean thematic inconsistency was that of the most experienced mappers, with nine percentage points. Experience had no significant effect on map inconsistency as a whole. Conclusion: Thematic inconsistency was high for all but the dominant thematic units, with potentially adverse consequences for mapping ecosystems that are fragmented or have low coverage. Interactions between site and mapping system properties are considered the main reasons why no relationships between scale and thematic inconsistency were observed. More controlled experiments are needed to quantify the effect of other factors on inconsistency in field‐based mapping. Abstract : Field‐based ecosystem maps often have high spatial uncertainty. We found that the area assigned to each ecosystem is considerably more reliable. Moreover, spatial uncertainty is highly influenced by site properties. In particular, mapping of ecosystems that are fragmented or have low coverage is associated with uncertainty.